Table of Content - - (Journal of Humanities & Social Sciences, 2024)
Table of Content1. Family Problems of Heart Patients, and the Medical Social Worker’s Role Facing Them A study applied to a sample of heart patients in Al-Madinah Al-Munawwarah HospitalsResearcher / Amna Ahmed Abdullah Harmoush2. Methods of Activating the Professional Role of the Social Worker in the Medical Sector:  An Applied Study on Social Workers in Government Hospitals in JeddahResearcher / Abdullah Abdulrahman Al-Qarni, Prof. Dr. Abdulrahman Abdullah Al-Omari3. The Indications of the Environmental in Wadi Al Ajradi in the Imam Turki bin Abdullah Reserve During the Holocene Period.Dr. Maha Awwad Alanazi4. The Role of Metamorphosis in Arabic Children’s LiteratureDr. Rafi’ Saed Yahya
Keywords: Journal of Human and Social Sciences